What interventions can improve quality of life or psychosocial factors of individuals with knee osteoarthritis? A systematic review with meta-analysis of primary outcomes from randomised controlled trials - Briani, Ronaldo Valdir [UNESP]; Ferreira, Amanda Schenatto [UNESP]; Pazzinatto, Marcella Ferraz [UNESP]; Pappas, Evangelos; Silva, Danilo De Oliveira; Azevedo, Fabio Micolis de [UNESP] (Bmj Publishing Group, 2018)
Objective To systematically review evidence of primary outcomes from randomised controlled trials (RCTs) examining the effect of treatment strategies on quality of life (QoL) or psychosocial factors in individuals with knee osteoarthritis (OA). Design Systematic review with meta-analysis. Data sources Medline, Embase, SPORTDiscus, the Cumulative Index to Nursing and Allied Health Literature (CINAHL) and Web of Science were searched from inception to November 2017. Eligibility criteria for selecting studies We included RCTs investigating the effect of conservative interventions on QoL or psychosocial factors in individuals with knee OA. Only RCTs considering these outcomes as primary were included. Results Pooled data supported the use of exercise therapy compared with controls for improving health-related and knee-related QoL. There was limited evidence that a combined treatment of yoga, transcutaneous electrical stimulation and ultrasound may be effective in improving QoL. Limited evidence supported the use of cognitive behavioural therapies (with or without being combined with exercise therapy) for improving psychosocial factors such as self-efficacy, depression and psychological distress. Summary/Conclusion Exercise therapy (with or without being combined with other interventions) seems to be effective in improving health-related and knee-related QoL or psychosocial factors of individuals with knee OA. In addition, evidence supports the use of cognitive behavioural therapies (with or without exercise therapy) for improving psychosocial factors such as self-efficacy, depression and psychological distress in individuals with knee OA.